YouTube’s Role in Destination Image Creation - Jakopović, Hrvoje (Journal of Education Culture and Society, 2020)
Contemporary promotion of tourist destinations represents a challenge and gives rise to many questions in a regard to numerous ways of communicating and transferring information. With concern to modern communication practices in society and due to fast-paced lifestyle, individuals are looking for information online and are making decisions based on available Internet data. Attracting tourists through traditional promotional techniques such as brochures, leaflets, printed guidebooks, fairs and festivals are unsufficient with a respect to the rising number of online users. Promotion of tourism is based on destination image which is created through direct or mediated experience and projected on the minds of individuals. It is greatly dependent on available information mostly visual. YouTube is a popular video sharing site that counts over one billion users. It gives open access to a great number of videos and therefore could have an important role in promoting tourist destinations. The website was firstly used for non-commercial purposes but today it is very attractive for advertisers. The author examines phenomena of YouTube and its potential for destination image creation. The aim of this article is to give an insight on characteristics of promotional videos used for tourism and to explore how various national and local tourist boards can use them on YouTube. The author identifies the public relations profession’s role in creation of promotional audio-visual material.